Anti-PD-1/PD-L1 immunotherapy in patients with solid organ transplant, HIV or hepatitis B/C infection. (November 2018) - Tio, Martin; Rai, Rajat; Ezeoke, Ogochukwu M.; McQuade, Jennifer L.; Zimmer, Lisa; Khoo, Chloe; Park, John J.; Spain, Lavinia; Turajlic, Samra; Ardolino, Luke; Yip, Desmond; Goldinger, Simone M.; et al.
Abstract: Background: Anti-programmed cell death protein 1/programmed death ligand 1 (PD-1/PD-L1) immunotherapy is now routinely used to treat several cancers. Clinical trials have excluded several populations, including patients with solid organ transplant, HIV infection and hepatitis B/C infection. We examined the safety outcomes of these populations treated with anti-PD-1/PD-L1 treatment in a multicentre retrospective study. Methods: Patients from 16 centres with advanced cancer and solid organ transplant, HIV infection or hepatitis B/C infection were included. Demographic, tumour, treatment, toxicity and outcome data were recorded. Results: Forty-six patients were included for analysis, with a median age of 60 years, and the majority of patients diagnosed with melanoma (72%). Among six patients with solid organ transplants, two graft rejections occurred, with one resulting in death, whereas two patients achieved partial responses. There were four responses in 12 patients with HIV infection. In 14 patients with hepatitis B, there were three responses, and similarly, there were three responses in 14 patients with hepatitis C. There was no unexpected toxicity in any viral infection group or an increase in viral load. Conclusion: Patients with HIV or hepatitis B/C infections treated with anti-PD-1/PD-L1 immunotherapy may respond to treatment without increased toxicity. Given the risk of graft rejection in solid organ transplant patients and also the potential for response, the role of anti-PD-1/PD-L1 immunotherapy needs to be carefully considered. Highlights: The efficacy/safety of anti-PD-1/PD-L1 therapy for cancer patients with organ transplant, HIV, or hepatitis B/C is unknown. 46 patients, including 6 patients with organ transplants, 12 patients with HIV,  and 14 patients each with hepatitis B and C were examined. Objective responses occurred in the HIV/hepatitis B/C cohorts without elevated or unexpected toxicities. 2 of 6 patients with organ transplants had graft rejection, including 1 death.